The Time Cost of Documents to Trade - Amin, Mohammad (2012)
This paper analyzes the relationship between the number of documents required to export and import and the time it takes to complete all procedures to trade. It shows that an increase in the number of documents required for export and import tends to increase the time cost of shipments. However, this relationship is far from simplistic, varying sharply in magnitude across rich versus poor countries and small versus large countries. Specifically, the increase in the time cost of increased documentation is much larger for relatively poor and larger countries. One interpretation of this finding is that richer countries that have more resources and smaller countries that rely more on trade invest more in building efficient documentation systems. Hence, in such countries relative to others, increased documentation adds less to the time cost at the margin. At a broader level, the findings suggest caution in interpreting how input-based measures such as the number of required documents to trade affect the quality of the business environment as far as the associated cost is concerned.